Constraining mountain front tectonic activity in extensional setting from geomorphology and Quaternary stratigraphy: A case study from the Matese ridge, southern Apennines - Valente, E.; Buscher, J.T.; Jourdan, Fred; Petrosino, P.; Reddy, Steven; Tavani, S.; Corradetti, A.; Ascione, A. (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Rugged peaks, large intermontane basins and frequent seismicity all characterize the active extensional tectonic setting of the southern Apennines. The Matese ridge typifies the active tectonic setting of the southern Apennines with steep carbonate mountain fronts and large depositional centres. Moderate to high magnitude earthquakes have affected the northern, western and eastern sectors of the Matese ridge in historical times. However, the seismogenic potential of the extensional fault system bounding the southern Matese mountain front has not been fully assessed to date. To unravel the active tectonic setting of the southern Matese mountain front, we have carried out a comprehensive geomorphological and tectonic-geomorphology investigation of the mountain front and its piedmont and have constrained results through chronological (i.e., tephrostratigraphical and 40Ar/39Ar) and structural data. Our study highlights that in the last ∼600 ka, activity along E-W trending normal faults has identified a locus of higher slip rate tectonic activity in the central part of the analysed mountain front. These active E-W-striking normal faults are inherited, reactivated structures, which have interacted with newly formed NW-SE-striking normal faults during NE-SW extension active on the regional scale, causing fault bending and local extension to be oriented N-S. Consequently, lower slip rates have been recorded along the NW-SE-striking normal faults at the north-western and south-eastern tips of the southern Matese front. The long-term displacement rate of the fault system at the boundary of the central part of the southern Matese front is consistent with mean values of displacement of faults that, in the southern Apennines, show evidence of activity during the late Quaternary. Despite strong historical seismicity clustering primarily around the study area, our data highlight that it cannot be ruled out that moderate to high magnitude seismicity could affect the southern Matese mountain front. Our case study represents an example of the possible modes of formation and evolution of mountain front-basin systems in extensional setting, and shows how the combination of different data sets allows unravelling the interaction between tectonic, erosional and sedimentary processes, which lead to landscape evolution of active mountain belts.